Enhancer RNA LINC00242-Induced Expression of PHF10 Drives a Better Prognosis in Pancreatic Adenocarcinoma - Tong, Wen; Zhu, Liuyang; Bai, Yi; Yang, Long; Liu, Zirong; Zhang, Yamin (Frontiers in Oncology, 2022)
Enhancer RNA is a kind of non-coding RNA, which is transcribed from enhancer region of gene and plays an important role in gene transcription regulation. However, the role of eRNA in Pancreatic adenocarcinoma (PAAD) still unclear. In this study, we identified the key eRNA and its target gene in PAAD. The transcriptome data and clinical information of pancreatic cancer were download from the UCSC Xena platform. A total of 2695 eRNAs and its target gene predicted by PreSTIGE method, were select as putative eRNA-target pairs. After survival analysis, we found that LINC00242 was the eRNA most related to patients’ survival, and correlation analysis further indicated that LINC00242 and its target gene PHF10 had a significant co-expression relationship. Down regulation of LINC00242 was significantly associated with unfavorable clinicopathological features. Based on pan-cancer analysis, we found that LINC00242 was associated with the survival of multiple cancers, and LINC00242 was co-expressed with its target genes in multiple cancer types. External experiments further demonstrated that PHF10 was the downstream target gene of LINC00242. After ssGSEA analysis, PAAD patients were classified as high, medium and low immune cell infiltration clusters. Compared with the low and medium immune infiltration clusters, the expression level of PHF10 was significantly up-regulated in the high immune infiltration clusters. After performing CIBERSOFT algorithm, we found that there was a significant difference in the abundance of immune infiltrating cells between the PHF10 high and low expression group. Additionally, the web tool TIMER was used to detect the distribution and expression of PHF10 in pan-cancer.